Index of Kumbakonam Using Top-K Query Retrieval Algorithm - Nagalakshmi, M; Vaishnavi, M (International Journal of Computer Sciences and Engineering, 2025)
Top-k denotes to the method which only returns the top K most important objects according to a given ranking function. To tackle the limitations of the existing Top-k query, we proposed a modified Top-k query algorithm. In this algorithm, we select the data elements which have higher ranking scores on each attribute, and then run a threshold controlling scheme on these data elements.This system reduces the manual and paper work. This proposed system will help the user to know the exact information and details of the facility that they are finding. This system is very much useful for all users. In the proposed system, the user can see the information’s of the facilities that are available in the various areas. The user can also see the top ten facilities that are available. And it is used to book travels ticket. And it’s contain the search button and corresponding textbox to search the particular information when the user click the search button it will be redirect to the related pages. The admin can add the additional information about the indexes of Kumbakonam. This system provides the addresses and information of the various facilities